PERANCANGAN FURNITUR SARANA DUDUK UNTUK MENCOBA SEPATU BAGI ANAK BERUSIA 3-5 TAHUN DI AREA KIDS ZONETOKO SEPATU - Desi Rut Suryani S.; Markus Hartono; Wyna Herdiana (CALYPTRA, 2018)
Abstract - Means of sitting in the area kids zone shoe store is a complementary tool that is used to facilitate the consumer as a prospective buyer is a child and parents. There are difficulties in doing shoe activities in the kids zone area of the shoe store, including the least-used children using existing sitting facilities, and parents tend to force the child to sit, and parents try to put the child's shoes on the bend position so that the parent's position is lower. Because it takes an attractive sitting facilities, with the position of the cradle according to the needs of children and parents. With a clear or noticeable shape, already known, more easily accepted, triggering fantasy so as not to limit children fantasize despite being in the activities of trying shoes. The existence of fantasy development in children make children use the means of sitting with their own will without coercion. The research method is qualitative method. Through research conducted with qualitative methods, it is known that the sitting facilities provided in the area kids zone shoe store, has a form that is less attractive for children and the unavailability of sitting facilities as needed parental seating position when trying to shoe for children. The purpose of this designed seating facility to make it easier for parents when trying to shoe for children, so that more efficient shopkeepers work. From the results of the research, will be designed a sitting facility that has a fantasy concept that will be combined with a classic design style. The concept of fantasy on the application of an attractive and clear or noticeable form so that when using the seat to provide the experience of children while driving a vehicle that has been known and remembered by children. The impression of the classic is to use the form of transportation with the formof classic, the old form is more clear (noticeable) with the completeness of tools such as aircraft propeller, boat rowing and the other.